1955
DOI: 10.1037/h0047218
|View full text |Cite
|
Sign up to set email alerts
|

Choice alternation: I. Stimulus vs. place vs. response.

Abstract: 1"Spontaneous allernalion" is a descriptive term which has been applied lo the often observed tendency of rats to behave in an orderly rather than a random fashion when presented with a Iwo-choice alternative more than once in close succession. Empirically, if an animal turns left in a T maze on its first trial, and if it is immediately returned to the starling point, the probability is quite high that it will turn right on the second trial.This systematic tendency to alternate choices has assumed considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

1960
1960
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 6 publications
0
36
0
Order By: Relevance
“…That is "resnonse was found to have little, if any, importance; place had a considerable importance; and the stimulus had more importance than place" (Walker, Dember, Earl and Karoly, 1955).…”
mentioning
confidence: 99%
“…That is "resnonse was found to have little, if any, importance; place had a considerable importance; and the stimulus had more importance than place" (Walker, Dember, Earl and Karoly, 1955).…”
mentioning
confidence: 99%
“…It is clear that normal animals rarely alternate responses (in the sense of left or right turns) per se, but rather alternate the place to which they go, or the particular stimuli they approach (e.g. Walker et al 1955). Alternation tends to increase as the animals are confined for longer periods in the initially chosen goal area, and it has been suggested that something akin to stimulus satiation accounts for this effect (Glanzer 1953b).…”
Section: Spontaneous Alternationmentioning
confidence: 99%
“…Pate & DeLoache (1970) stated that several investigators (Glanzer, 1953;O'Connell, 1964;Walker, Dember, Earl, & Karoly, 1955) claimed to have found spontaneous alternation of visual stimuli. This is one-third incorrect.…”
Section: Referencesmentioning
confidence: 99%